‘How low can you go?’ Developers’ perspectives on involving young children in the development of patient reported outcome measures - Victoria Gale; Philip A. Powell; Jill Carlton (Journal of Patient-Reported Outcomes)
Abstract Background Recommendations suggest that children need to be ≥ 8 years-old to participate in concept elicitation (CE) and cognitive interviewing (CI) when developing patient reported outcome measures (PROMs). However, these recommendations have not been subject to thorough scrutiny and recent evidence suggests that younger children may be enabled to participate. This study audited current opinions of PROM developers regarding the feasibility of conducting CE and CI research with children. Methodology An online survey was developed to capture PROM developers’ perspectives, recruited from existing networks (UK PROMs, International Society for Quality of Life Research) and outcomes research groups from English-speaking countries between August-November 2024. Survey questions explored the ages from which developers considered it feasible to include children in CE and CI research, their previous experiences conducting CE/CI research with children, and respondents’ background experiences with children. Results were analysed descriptively, and exploratory comparisons were made based on developers’ characteristics. Results Fifty-eight responses were analysed. The mean youngest ages considered feasible to include children in CE and CI research were 6.66 years and 7.36 years, respectively. The mean youngest ages respondents reported involving children in CE and CI research in practice were 7.67 years and 8.13 years, respectively. Concern that children would have insufficient cognitive and/or linguistic skills was the most often endorsed reason for considering the involvement of younger children to be infeasible. Respondents who had recent parental experience with younger children tended to consider it feasible to include children from younger ages. Those who had conducted CI with children considered it feasible to include children in CI from younger ages. Opposingly, those who had conducted CE with children considered it less feasible to include younger children in CE research. Conclusions In-line with established precedent, PROM developers included children from ∼ 8 years-old in CE and CI research, while in principle considering it feasible to include younger ages. Reasons for including (or not including) certain age groups in CE and CI research need critical evaluation and PROM developers may wish to consider ways in which more inclusive opportunities for younger children can be provided.